Star Excursion Balance Test (SEBT): Comparison of Results with and without Neuromuscular Ankle Bandage - Alvaro Zamorano; Jair Burboa; Diego Cuzmar; Jose Hun; Guillermo Robles; Maximiliano Barahona; Jaime Hinzpeter (International Physiology Journal, 2018)
Study Design: Prospective study, simple crossover design. Background: Proprioception is a cornerstone for maintaining joint and postural stability. Dynamic stability is particularly emphasized within these components. This feature is important in the rehabilitation field. Therefore, the quest for elements to improve these values ​​can bring advantages in sports. Objectives: Evaluate if there are advantages in the performance of a Star Excursion Balance Test (SEBT) using Kinesio taping. Methods: We evaluated 10 professional soccer players from the Chilean women’s national team. They were randomly divided into 2 groups. One group had Kinesio taping and their SEBT performance was evaluated. The other group performed the measurements without the use of Kinesio Taping. Afterward, each group performed the evaluation they did not do during the first stage. We then compared the performance achieved with and without the use of Kinesio Taping Results: There were significant differences in the performance achieved by the players who had the SEBT bandage applied in comparison to the players that did no. This was confirmed by using the non-parametric Wilcox test for each of the SEBT positions. Conclusions: Kinesio taping has positive implications in the SEBT. We can extrapolate that its use can improve the dynamic balance and thus become an important pillar in sports rehabilitation.
Keywords: dynamic stability